Glucose mitigates propionate toxicity and enhances odd-chain fatty acid production in Schizochytrium sp.: mechanistic insights and rational fermentation design - Ziliang Deng; Zhao Zhang; Shuang Sun; Zihan Meng; Yaqi Xu; Min Gao; Jiayi Li; Ang Li; Weijia Li; Dongzhe Sun (Bioresource Technology, 2026)

Occurrence and behaviors of organophosphate esters in shallow grass-type lake ecosystems: The key role of aquatic plants - Mei Wang; Bing Wang; Yifan Zhang; Yihang Sun; Jingjing Zhao; Ang Zhao; Chao Wei (Water Research, 2026)

Overcoming thermodynamic limitations on anaerobic methanogenesis via DSF/c-di-GMP enhanced indirect interspecies electron transfer - Chunyan Li; Jia Meng; He-Ping Zhao; Ang Li (Water Research, 2026)

MAAI -YOLOv11s: A novel microplastic and nanoplastic particle classification and detection method in microfluidic chip with an improved YOLOv11s model - Kai Zhao; Junzhu Yao; Ang Li; Xuyang Wang; Jingbo Li; Yiyang Huo; Jie Chen; Junsheng Wang (Journal of Water Process Engineering, 2026)

Development of a global integrated environmental quality index for population health research - Wenjie Ruan; Qi Zhao; Xiaoyue Liu; Lina Ang; Haitong Zhe Sun; Wei Jie Seow (Environmental Pollution, 2026)

Canned seafood as a potential source of microplastics exposure with taxon-specific partitioning and packaging-derived contamination - Xinyi Li; Shihan Xu; Jin Qian; Binhan Li; Li'ang Li; Chengming Zhang; Fangzheng Zhang; Menghong Hu; Moslem Sharifinia; Nisha Singh; Jae-Seong Lee; James Kar-Hei Fang; et al. (Environmental Pollution, 2026)

Adaptive sideslip angle fusion estimation and state-feedback path-tracking control for agricultural tractors - Shiting Lyu; Jian Zhang; Yunhao Shi; Danyang Lyu; Ranbing Yang; Ang Zhao (Computers and Electronics in Agriculture, 2026)

Hydrodynamic interference and load evolution of staggered cylinder pairs under dam-break waves: An active learning-based Kriging modeling framework - Zhengjie Wu; Ang Liu; Yong Xu; Zexing Jiang; Bingling Wang; Yuanmin Zhao; Guoji Xu (Ocean Engineering, 2026)

Zinc co-exposure with different antibiotic classes drives distinct microbial community restructuring in activated sludge - Yu Ang Li; Shijie Dong; Yongchao Li; Wei Wen; Mengbo Yuan; Jiangxiao Luo; Bin Shi; Renxin Zhao (Journal of Hazardous Materials, 2026)

Hypoxia-induced downregulation of cAMP drives Ganoderic acid biosynthesis and restricts biofilm development in Ganoderma lucidum - Siyi Wang; Li Tian; Faqin Li; Qin Wang; Yanan Tan; Yanda Ning; Xuewei Cao; Yueqian Liu; Jiaolei Shangguan; Huihui Li; Ailiang Jiang; Mingwen Zhao; et al. (Food Research International, 2026)

Activating lattice oxygen in Ni-doped SnO2 to break surface confinement for high-performance hydrogen sensing - Meili Wu; Yanbai Shen; Sikai Zhao; Ang Li; Jinzhou Bai; Qiang Zhao; Wenbao Liu; Zhenyu Yuan; Fanli Meng (Chemical Engineering Journal, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

The Effects of Intraoperative Hypotension on Postoperative Acute Kidney Injury and Myocardial Injury: A Systematic Review and modelling study - Jiaxin Zhao; Xuan Li; Yunfei Lv; Rui Zhang; Ang Li; Gang Dong (Phenomics, 2026)

Organophosphate triesters and diesters in the Yellow River Basin (Shandong section): Geographical patterns, land use correlates and compound-specific source apportionment - Yuting Ren; Lin Zhu; Huijie Dang; Lili Cui; Ang Zhao; Chao Wei; Mei Wang (Marine Pollution Bulletin, 2026)

Microbial community shift and functional reorganization from influent to effluent in wastewater treatment plants on the Qinghai–Tibet Plateau - Yongchao Li; Bin Shi; Di Li; Yu-Ang Li; Mengbo Yuan; Jiangxiao Luo; Shijie Dong; Wei Wen; Renxin Zhao (Journal of Environmental Management, 2026)

Molecular bridging-enables fully π-conjugated carbonyl polymers for selective ammonium ion capture in capacitive deionization - Yuxi Huang; Jun Yang; Hao Zhou; Tingliang Yuan; Jinyang Peng; Xinran Zhao; Chunyan Li; Minjie Shi; Edison Huixiang Ang (Chemical Engineering Journal, 2026)

Revealing thermoelectric property-performance correlations for the design of self-powered sensors - Zijian Lin; Bangzhou Tian; Xiaobo Tan; Chuke Zhao; Jiaxing Luo; Zhilong Zhao; Fan Feng; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2026)

Competitive adsorption performance of volatile organic compounds on ZSM-5: Key influence factors and mechanisms - Yanling Zhao; Huan Liu; Ang Gao; Zhong Ji; Haoyue Zhang; Hao Huang; Lejin Xu; Hong Yao (Chemical Engineering Journal, 2026)

Microbial metabolism regulates the stabilization of rhizodeposition-derived carbon in soil aggregates and mineral fractions under long-term tillage - Wen-Sheng Liu; Ben-Shun Liu; Zi-Ang Wang; Yong-Qiang Xu; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2026)

The dual nature of neuroticism: distinct dimensions impact longevity and well-being - Yini He; Jing Xiao; Ke Hu; Tian Gao; Yan Yan; Yu Yu; Lei Wang; Kaixin Li; Wenkun Lei; Kun Zhao; Changsheng Dong; Xiaohan Tian; et al. (Science Bulletin, 2026)

Chlorine dioxide fumigation induces transcriptomic and metabolomic reprogramming enhancing resistance to soft rot in kiwifruit - Ang Li; Shuang Luo; Di Feng; Xiaoya Chen; Zhidan Zhao; Tiantian Li; Yunhe Meng; Xiaoqin Yang; Yunjiang Cheng; Yunliu Zeng (Postharvest Biology and Technology, 2026)

Sustainability potential of landfill mining and resource recovery: Evidence from plant cases, provincial data, and life cycle assessment in China - Ang Wang; Jing Li; Wenxin Xue; Yin Li; Hanqiao Liu; Jifeng Zhao; Qianlong Han (Journal of Environmental Chemical Engineering, 2026)

A proof of concept study of electrocoagulation powered by an electro-wetland for hexavalent chromium removal from wastewater - Xiaorui Lei; Yaqian Zhao; Ting Wei; Yi Mao; Fuhao Zhang; Ang Liu; Yujie Yuan (Chemical Engineering Journal, 2026)

Characteristics and drivers of net ecosystem CO2 exchange in the Badain Jaran Desert - Ping Yang; Hang Zhao; Jinqiao Liu; Qingfan Song; Zhenmin Niu; Nai’ang Wang (Theoretical and Applied Climatology, 2026)

HUTG: a next-generation IGS real‑time combined GIM via two‑step global and regional correction with robust weighting from HENU and UPC‑IonSAT - Kualong Xu; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Germán Olivares-Pulido; David Roma-Dollase; Alberto García-Rigo; Ningbo Wang; Zishen Li; Ang Liu; Clément Ubelmann; et al. (GPS Solutions, 2026)

A lightweight vision based method for pre storage potato sorting in an automatic grading system - Danyang Lv; Mengdi Cheng; Ang Zhao; Ranbing Yang; Yongfei Pan; Shiting Lv; Jian Zhang; Tao Wang (Journal of Stored Products Research, 2026)

Exploring advanced measures of constructed wetland for the improved removal of emerging contaminants - Ang Liu; Yaqian Zhao; Jiwei Zhu; Ting Wei; Kaiyue Hao; Liu Yang; Carlos A. Arias; Juan A. Baeza (Journal of Environmental Management, 2026)

Combining nontarget and target analysis to determine organic pollutants in secondary copper and aluminum smelter fly ash - Zeyin Peng; Dan Xia; Shuangshuang Zhao; Ang Zhao; Dongdong Zhang; Yuhao Sun; Yifei Sun (Journal of Environmental Sciences, 2026)

Double-defect ZnO aerogel-supported single-atomic ruthenium for selective gas-solid phasephotooxidation of methane to methanol - Xiaochao Xu; Xiangxia Wu; Zhen Xiao; Zhi-Ang Zhao; Guanwei Peng; Jinni Shen; Lifang Yang; Wenxin Dai; Zizhong Zhang (Chemical Engineering Journal, 2026)

Development and application of a distributed hydrology and soil erosion model in a semi-arid catchment, China - Ang Lu; Peng Tian; Guangju Zhao; Xingmin Mu; Xiaojing Tian; Chaojun Gu; Lin Yang; Junjian Fan (CATENA, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Chronology of Tamarix nebkha formation reveals historical desertification processes in ancient oases of the Hexi region, northeastern Tibetan Plateau - Liqiong Bai; Nai’ang Wang; Yinzhou Huang; Hang Zhao; Hao Ye; Yixin Wang; Yuchen Wang; Xiaoyang Zhao (CATENA, 2026)

ALM-LED: autonomous LiDAR mapping in underground space with Luojia explorer anti-collision drone - Shangzhe Sun; Chi Chen; Bisheng Yang; Yuhang Xu; Leyi Zhao; Yong He; Ang Jin; Liuchun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A non-invasive continuous glucose monitoring method based on the Bergman minimal model - Ang Li; Long Zhao; Chenyang Wu; Zhanxiao Geng; Lihui Yang; Fei Tang (Medical & Biological Engineering & Computing, 2025)

Impact of Fluid Sloshing on BOG Generation in Type B LNG Tanks During Ship Emergency Stops - Haikang Zhao; Gang Wu; Jiachen Chen; Xigang Pu; Sicong Wang; Yuhao Yuan; Ang Sun (Journal of Marine Science and Engineering, 2025)
The safe and efficient transport of Liquefied Natural Gas (LNG) is critically dependent on understanding fluid dynamics within cargo tanks, which directly influence structural integrity and operational safety. Study employs the Volume of Fluid (VOF) method to simulate fluid sloshing and phase change dynamics in Type B LNG cargo tanks during emergency stop conditions. The transient simulations employ a time step of 5 × 10−3 s, a model with 46,840 grids, and the analysis focuses on impact forces on tank walls, their dependence on filling levels. Results show that the flow disturbance caused by vessel rolling increases BOG generation fluctuations by approximately 35%. Sloshing significantly increases BOG generation, particularly after a 10 s relaxation period, as the initial shock enhances heat transfer and mixing, accelerating vapor production. Original components of LNG are sensitive to BOG generation and impact forces on the front bulkhead are significantly higher than on the rear, with peak impacts occurring. The filling rate is a critical parameter influencing fluid dynamics and safety in LNG transportation. Impact magnitude increases with fill level up while at about 80% it declines; impact timing shortens at higher fill ratios. A BOG generation mechanism in which microscale turbulence and ongoing thermal imbalance govern the kinetics of evaporation phase transitions was proposed. It was discovered that the impact forces and BOG production exhibit rise–fall–rise patterns driven by impact dynamics, condensation, and evaporation processes. The findings highlight the critical role of fluid sloshing in affecting tank safety and operational efficiency, offering insights into designing more resilient LNG cargo tanks and optimizing transportation safety and economy.

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Development and characterization of magnetic cellulose adsorbents functionalized with polyacrylic acid - Chengmin Hou; Zi'’ang Zhao; Fanglin Li; Yuan Bai; Chuangchuang Ren; Chenyu Li; Ze Fan; Wanting Jia; Ying Zhang; Weimin Yan; Yuru Li; Yiting Yang; et al. (Journal of Water Process Engineering, 2025)

Metals and polycyclic aromatic hydrocarbons co-exposure: Amino acid omics insights on blood glucose homeostasis - Jiaxin Zhao; Ming Yang; Xiaoqing Xing; Yayuan Mei; Quan Zhou; Meiduo Zhao; Jing Xu; Yanbing Li; Kai Li; Qun Xu; Ang Li (Journal of Environmental Sciences, 2025)

Assessing the human health risks from organophosphate esters: exposure assessment via wild freshwater fish consumption - Shuhui Wang; Ang Zhao; Bing Wang; Yifan Zhang; Qian Han; Emi Yang; Haode He; Chao Wei; Yuxia Yang; Jianzhong Xu; Mei Wang (Food Chemistry, 2025)

Unveiling critical drivers of soil salinity prediction accuracy in remote sensing: a global meta-analysis - Zi’ang Cui; Ruiqi Zhang; Wenhui Wang; Zhaoce Peng; Yifan Wu; Ziyue Zhao; Mohan Li; Yutong Cong; Shaoyan Zhang; Zhenhai Li; Lijing Han; Jianli Ding (Plant and Soil, 2025)

Estimating rainfall intensity from surveillance audio: A hybrid model-data-driven framework - Xing Wang; Kun Zhao; Haiqin Chen; Ang Zhou; Jiuwei Zhao; Shuaiyi Shi; Thomas Glade (Journal of Hydrology, 2025)

Rational design of SnO2 quantum dots/SnS2 hybrids for enhanced NO2 sensing at room temperature: Insights from DFT and in-situ DRIFTS - Jinzhou Bai; Yanbai Shen; Ang Li; Meili Wu; Siyao Liu; Wenbao Liu; Qiang Zhao; Sikai Zhao; Fanli Meng (Chemical Engineering Journal, 2025)

Waterworks sludge coupled with biochar and pyrite as wetland substrates for enhanced nitrogen removal and greenhouse gases mitigation: First study on synergistic mechanisms - Yujie Yuan; Yaqian Zhao; Tao Zhang; Ting Wei; Yamei Cai; Lei Yang; Jingmiao Fu; Ang Liu; Anran Yang (Chemical Engineering Journal, 2025)

Recent advances of constructed wetlands utilization under cold environment: Strategies and measures - Kaiyue Hao; Yaqian Zhao; Ting Wei; Du Wen; Ang Liu; Yulong Huang; Zhenzhen Chen (Process Safety and Environmental Protection, 2025)

Femtosecond laser-induced myocardial incision: Preclinical study towards new tools for precision cardiac surgery - Ang Liu; Tong Xia; Siyuan Cao; He Zhao; Yubin Hou; Xuejing Duan; Li Li; Ke Wang; Pu Wang; Chaowu Yan (Journal of Photochemistry and Photobiology B: Biology, 2025)

Standing at the crossroads: How does amino acids function in the crosstalk between pancreas and the kidney under exposure to per- and polyfluoroalkyl substances? - Ming Yang; Ziwen An; Xiaoqing Xing; Yayuan Mei; Haoran Li; Jiaxin Zhao; Zhenzhen Tan; Yanbing Li; Jingjing Zhao; Jiayin Zhao; Meiduo Zhao; Jing Xu; et al. (Journal of Hazardous Materials, 2025)

Effect of PFAS serum exposure pattern on the lipid metabolism: Time to step-forward in causal inference in epidemiology - Ming Yang; Ang Li; Yayuan Mei; Haoran Li; Ziwen An; Quan Zhou; Jiaxin Zhao; Yanbing Li; Kai Li; Meiduo Zhao; Jing Xu; Huicai Guo; et al. (Journal of Environmental Sciences, 2025)

Integrated multiscale topology optimization of frame structures for minimizing compliance - Kui Liu; Kirk Ming Yeoh; Yehui Cui; Ang Zhao; Yangjun Luo; Zheng Zhong (Engineering Structures, 2025)

Quantifying graphitic curvature and engineering closed pores in phenolic resin hard carbons for enhanced plateau capacity in sodium-ion batteries - Xiaotian Li; Jiapeng Zhang; Renlu Yuan; Boyang Zhao; Chuang Qiu; Dengke Wang; Man Yuan; Ang Li; Haiyan Liu; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Revealing the ionic storage mechanisms of Mo2VC2Tz (MXene) in multiple aqueous electrolytes for high-performance supercapacitors - Xiaodie Xuan; Yangyang Xie; Yi Tang; Jianghong Zhou; Zhao Bi; Junhui Zou; Yu-ang Lei; Jiahang Gao; Lu Li; Aibo Zhang; Chenhui Yang (Chemical Engineering Journal, 2025)

Microbial Responses to Temperature Change Mediated by Nutrient Enrichment - Wenqian Zhao; Ang Hu; Janne Soininen; Jianjun Wang (Global Ecology and Biogeography, 2025)
Aim Understanding of the mechanisms in community reorganisation and predicting species distribution are challenging because species responses to warming vary notably. We assessed thermal responses of aquatic bacterial communities in 167 stream biofilms and 480 field aquatic microcosms on subtropical and temperate mountainsides with contrasting climates, and examined the joint effects of temperature and nutrients on thermal responses. Location Galong and Qilian mountains of the Tibetan Plateau, China. Time Period July to September in 2018. Major Taxa Studied Bacteria. Methods We examined bacterial communities using high‐throughput sequencing. We quantified aggregated thermal responses of bacterial communities for each sample based on changes in species abundance along temperature gradients. Finally, we studied the effects of temperature change and nutrient enrichment on thermal responses using structural equation models. Results Bacterial species showed consistent responses to temperature change within each climate zone in streams or microcosms. The magnitude of positive and negative thermal responses increased and decreased with lower rRNA operon copy numbers, respectively. In the two contrasting climate zones, the community‐level thermal responses consistently increased with rising temperatures. Bacterial phyla and classes with diverse species thermal responses showed greater sensitivity of thermal responses to warming. Unexpectedly, thermal responses were more sensitive to warming at higher and lower nutrients in the subtropical wet and the temperate arid climate zones, respectively. The divergence is explained by the fact that nutrients showed stronger effects on thermal responses in the temperate arid than in the subtropical wet climate zones, while temperature was dominant in both climate zones. The result was consistent in streams and microcosms. Main Conclusions Our synthesis across two contrasting habitats and climates clearly shows consistent patterns in microbial thermal responses along temperature gradients. Sensitivity of thermal responses to warming is mediated by nutrient enrichment. Our findings provide a novel understanding of aquatic microbial biodiversity responses to global change.

Variability of urinary metal in short-, mid-, long-term periods and its optimal sampling strategy: A novel epidemiological insight to exposure classification - Yanbing Li; Liu Liu; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Ming Yang; Lingli Sun; Ang Li; Qun Xu (Environmental Research, 2025)

Sulfur-bonded hard carbon with enhanced interfacial and bulk kinetics for potassium-ion hybrid capacitors - Chuang Qiu; Anuj Kumar; Mohammad Tabish; Xinzhuo Mai; Liewen Guo; Ying Zhao; Yibo Zhu; Ang Li; Ghulam Yasin; Xiaohong Chen; Huaihe Song (Chemical Engineering Journal, 2025)

Ecological health assessment of urban rivers in the middle temperate zone based on the improved TOPSIS model — a case study of the Yitong River in China - Ke Zhao; Mingxuan Bai; Ang Dong; Mengnan Shen (Environmental Monitoring and Assessment, 2025)

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Multiplex quantitative PCR assay for porcine circoviruses 2 and 3 and its application for measuring infection rates at different stages of pig production - Zhen Li; Shuaiyin Guan; Jiaying Zhao; Yuhuan Chen; Yang Han; Ang Tian; Saisai Zhou; Huanchun Chen; Yunfeng Song (Archives of Virology, 2025)

Utilization and perspectives of electricity generated from electro-wetland - Xiaorui Lei; Yaqian Zhao; Asheesh Kumar Yadav; Ang Liu; Yi Mao; Dan Wei; Fuhao Zhang; Xuechen Bai; Pratiksha Srivastava (Journal of Environmental Chemical Engineering, 2025)

Enhanced lithium extraction from high-sodium brines: Modification of a manganese-based ion sieve using hydroxylated graphene and graphene oxide - Ang Mi; Xinbo Qin; Fei Zhang; Rongping Yun; Youjing Zhao; Min Wang; Xu Xiang (Desalination, 2025)

Experimental study of thermal comfort by variable temperature and velocity air supply system in operating room - Bin Zhou; Ang Wang; Hui Ren; Jie Xia; Fan Peng; Shao-Cong Wang; Yi-Chu Wang; Hao-Yi Zhao; Wen-Jie Li; Mei-Lan Tan; Risto Kosonen (Building and Environment, 2025)

Cohort Profile: Precision Environmental Health Cohort of Healthy Undergraduates - Yanbing Li; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Ming Yang; Liu Liu; Huicai Guo; Qun Xu; Ang Li (Phenomics, 2025)

Water Use Efficiency of Grassland Ecosystem in Badain Jaran Desert and Its Relations to Biometeorological Variables - Nan Meng; Nai’ang Wang; Liqiang Zhao; Xiaojun Liu; Jinqiao Liu; Sung-Ching Lee (Ecosystems, 2025)

Biological functions and molecular mechanisms of circHIPK3 in digestive system tumors - Jian Li; Xin Su; Xiao Xu; Youbao Ye; Cailiu Wang; Ang Liu; Changchun Zhao; Wenxiu Liu; Liwen Yang; Tao Wang; Xiangyong Hao (Human Cell, 2025)

Comparative analysis of femtosecond, picosecond, and nanosecond laser techniques for transseptal puncture: An in vitro study with pathological correlation - Ang Liu; Tong Xia; Siyuan Cao; He Zhao; Yubin Hou; Xuejing Duan; Li Li; Ke Wang; Pu Wang; Chaowu Yan (Journal of Photochemistry and Photobiology B: Biology, 2025)

Photothermal halloysite nanotube hybrids with CoO/carbon layers for enhanced pollutant degradation and solar-powered water purification - Yifang Zhang; Hongyao Zhao; Jiayi Zhou; Yanyun Wang; Yangping Zhang; Jialing Shen; Danhong Shang; Feng Zeng; Jianming Pan; Yiyan Song; Fu Yang; Edison Huixiang Ang (Desalination, 2025)

Probing the microwave induced overheating at electrode surface using a combined electrochemical and fluorescence method - Zongliang Kou; Zhenyu Zhao; Hong Li; Ang Li; Kai Liu; Xiaolei Fan; Xin Gao (Chemical Engineering Journal, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

Role of per- and polyfluoroalkyl substances in the cardiorenal system: Unraveling crosstalk from the network of pollutants and phenotypes - Ming Yang; Jiaxin Zhao; Ziwen An; Haoran Li; Chaoying Ma; Junli Lv; Fang Xiao; Zhenzhen Tan; Longfei Li; Xiaoguang Zhang; Xuehui Liu; Yi Liu; et al. (Journal of Environmental Sciences, 2025)

Identification of elite alleles associated with glume-opening angle in rice natural population - Yingying Zhao; Hui Jiang; Chunyu Jing; Tianhu Li; Yanan Zhang; Zhengbo Liu; Yinping Chang; Mingyu Du; Hao Sun; Jinghan Sun; Yang Ang; Xianping Cheng; et al. (Euphytica, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Trait–environmental relationships reveal microbial strategies of environmental adaptation - Minglei Ren; Ang Hu; Zhonghua Zhao; Xiaolong Yao; Ismael Aaron Kimirei; Lu Zhang; Jianjun Wang (Ecology, 2025)
Microbial trait variation along environmental gradients is crucial to understanding their ecological adaptation mechanisms. With the increasing availability of microbial genomes, making full use of the genome‐based traits to decipher their adaptation strategies becomes promising and urgent. Here, we examined microbial communities in water and sediments of 20 East African lakes with pH values ranging from 7.2 to 10.1 through taxonomic profiling and genome‐centric metagenomics. We identified functional traits important for microbial adaptation to the stresses of alkalinity and salinity based on the significant trait–environment relationships (TERs), including those involved in cytoplasmic pH homeostasis, compatible solute accumulation, cell envelope modification, and energy requisition. By integrating these significant traits, we further developed an environmental adaptation index to quantify the species‐level adaptive capacity for environmental stresses, such as high pH environments. The adaptation index of pH showed consistently significant positive relationships with species pH optima across regional and global genomic datasets from freshwater, marine, and soda lake ecosystems. The generality of the index for quantifying environmental adaptation was demonstrated by showing significant relationships with the species niche optima for the gradients of soil temperature and seawater salinity. These results highlight the importance of TERs in facilitating the inference of microbial genomic‐based adaptation mechanisms and expand our understanding of ecological adaptive strategies along environmental gradients.

Effects of Ammonia loading and oxygen flux on nitrogen removal in a PNA-coupled MABR - Jiang-Feng Zhang; Jinfeng Bao; Chun-Yu Lai; Chen Zhou; Ang Li; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Establishment and Characterization of Bisexually Fertile Triploid Dwarf Surf Clam Mulinia lateralis - Ang Zhao; Zujing Yang; Haoran Wang; Hao Wang; Shuai Zhong; Chenhui Li; Yuehuan Zhang; Jingjie Hu; Zhenmin Bao; Xiaoting Huang (Marine Biotechnology, 2025)

Thermoelectric cooling and low-temperature power generation in n-type PbTe enabled by band flattening and entropy engineering - Qian Deng; Jiansen Wen; Xiang An; Yin Xie; Jiaxing Luo; Zhilong Zhao; Baisheng Sa; Hongliang Dong; Ran Ang (Chemical Engineering Journal, 2025)

Methane emissions from the riverine sandy wetlands on the Mongolia Plateau - Ang Li; Zun-Lan Luo; Katerina Machacova; Song Zhao; Jin-Chao Feng; Xing-Guo Han; Zhi-Ping Wang (Environmental Monitoring and Assessment, 2024)

Biogenic amorphous FeOOH activated additional intracellular electron flow pathways for accelerating reductive dechlorination of tetrachloroethylene - Yang Yu; Ang Li; Sheng-Qiang Fan; He-Ping Zhao (Water Research, 2024)

Effect of the LIF gene on the cell cycle and apoptosis of ovarian granulosa cells in white Muscovy ducks - Qing-hua Tao; Ning-ning Sun; Meng-shi Wang; Wan-xin Zhao; Wei Liu; Xu Zhang; Ang Li (Theriogenology, 2024)

Construction of a synthetic anaerobic dechlorination microbiome to degrade chlorinated ethenes by application of metabolic interactions principle - Zeyi Wang; Yang Yu; Rongjian Zhao; Ang Li (Science of The Total Environment, 2024)

A novel perlucin with immune regulatory functions protects Litopenaeus vannamei against Vibrio parahaemolyticus infection - Zi-ang Wang; Linwei Yang; Zexu Zhao; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2024)

Synergistic regulation of dual thresholds: Hydroxyl occupancy and carbon species in the targeted catalytic hydrocracking of lignite - Cong Liu; Zhi-Ang Liu; Zhong-Qiu Liu; Hai-Ni Yang; Guo-Xiao-Yao Zhao; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Acidic proteomes are linked to microbial alkaline preference in African lakes - Minglei Ren; Ang Hu; Lu Zhang; Xiaolong Yao; Zhonghua Zhao; Ismael Aaron Kimirei; Jianjun Wang (Water Research, 2024)

Disturbed glucose homeostasis and its increased allostatic load in response to individual, joint and fluctuating air pollutants exposure: Evidence from a longitudinal study in prediabetes - Yayuan Mei; Ang Li; Jiaxin Zhao; Yanbing Li; Quan Zhou; Ming Yang; Meiduo Zhao; Jing Xu; Kai Li; Guohuan Yin; Jingtao Wu; Qun Xu (Science of The Total Environment, 2024)

Formation mechanism and geophysical properties of fracture-filling gas hydrate in the host sediments: A comprehensive review - Gaowei Hu; Zhun Zhang; Yapeng Zhao; Qingtao Bu; Ang Li; Wengao Zhao; Zihao Wang; Xiaoqian Qiu; Tong Liu; Shengbiao Liu; Wanjun Lu; Nengyou Wu (Earth-Science Reviews, 2024)

Efficient catalysis for acidic methanol oxidation: Exploration of a Low-Platinum quaternary alloy catalyst via a Two-Step method - Shuaiqi Li; Zi'ang Fan; Yulong Li; Yue Zhang; Youxin Zhao; Jingxiang Zhao; Jingjia Zhang; Zhenbo Wang (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Association Between Metal Exposure and Mitochondrial DNA Parameters and the Potential Mediation Effect of Oxidative Stress - Jing Xu; Meiduo Zhao; Xiaoyu Ge; Xiaolin Liu; Lanping Wei; Ang Li; Yayuan Mei; Guohuan Yin; Jingtao Wu; Qun Xu (Exposure and Health, 2024)

High-intensity exercise training in large yellow croaker is a compromise between disease resistance and fish welfare - Junjia Zeng; Ang Qu; Yacheng Deng; Pengxin Jiang; Ji Zhao; Jiaying Wang; Yue Liu; Wei Liu; Qiaozhen Ke; Fei Pu; Yaxian Li; Peng Xu (Aquaculture, 2024)

Identifying climate refugia for wild yaks (Bos mutus) on the Tibetan Plateau - Hang Zhao; Hongyi Cheng; Nai'ang Wang; Liqiong Bai; Xiaowen Chen; Xiao Liu; Bin Qiao (Journal of Environmental Management, 2024)

Mo4/3B2Tx induced hierarchical structure and rapid reaction dynamics in MoS2 anode for superior sodium storage - Guilong Liu; Wenzhuo Yuan; Zihan Zhao; Jin Li; Naiteng Wu; Donglei Guo; Xiao Liu; Yong Liu; Ang Cao; Xianming Liu (Chemical Engineering Journal, 2024)

Effects of Gene Alternative Splicing Events on Resistance to Cryptocaryonosis of Large Yellow Croaker (Larimichthys crocea) - Xin Li; Qiaozhen Ke; Ang Qu; Jiaying Wang; Ji Zhao; Peng Xu; Tao Zhou (Marine Biotechnology, 2024)

The structure of bacteria–fungi bipartite networks along elevational gradients in contrasting climates - Wenqian Zhao; Janne Soininen; Ang Hu; Jinfu Liu; Mingjia Li; Jianjun Wang (Molecular Ecology, 2024)
Climate change is altering species distribution and modifying interactions in microbial communities. Understanding microbial community structure and their interactions is crucial to interpreting ecosystem responses to climate change. Here, we examined the assemblages of stream bacteria and fungi, and the associations between the two groups along elevational gradients in two regions with contrasting precipitation and temperature, that is the Galong and Qilian mountains of the Tibetan Plateau. In the wetter and warmer region, the species richness significantly increased and decreased with elevation for bacteria and fungi, respectively, while were nonsignificant in the drier and colder region. Their bipartite network structure was also different by showing significant increases in connectance and nestedness towards higher elevations only in the wetter and warmer region. In addition, these correlation network structure generally exhibited similar positive association with species richness in the wetter and warmer region and the drier and colder region. In the wetter and warmer region, climatic change along elevation was more important in determining connectance and nestedness, whereas microbial species richness exerted a stronger influence on network structure and robustness in the drier and colder region. These findings indicate substantial forthcoming changes in microbial diversity and network structure in warming climates, especially in wetter and warmer regions on Earth, advancing the understanding of microbial bipartite interactions' response to climate change.

Association between PM2.5 constituents and cardiometabolic risk factors: Exploring individual and combined effects, and mediating inflammation - Jiaxin Zhao; Yayuan Mei; Ang Li; Quan Zhou; Meiduo Zhao; Jing Xu; Yanbing Li; Kai Li; Ming Yang; Qun Xu (Chemosphere, 2024)

Tuning quantum dots emission on DNA tetrahedron/silica nanosphere/graphene oxide nanointerface for ratiometric fluorescence assay of Pb2+ in multiplex samples - Manting Li; Haikun Luo; Zhao Wang; Qian Mo; Shanshan Zhong; Yu-ang Mao; Shuting Li; Xinchun Li (Analytica Chimica Acta, 2024)

Can xenobiotics support the growth of Mn(II)-oxidizing bacteria (MnOB)? A case of phenol-utilizing bacteria Pseudomonas sp. AN-1 - Aonan Qiao; Haixia Pan; Jiaxi Zang; Yiwen Zhang; Xianliang Yi; Yang Liu; Jingjing Zhan; Xiaojing Yang; Xu Zhao; Ang Li; Hao Zhou (Journal of Hazardous Materials, 2024)

Application of Artificial Neural Network to Evaluate Coalbed Methane Exploration Potential: A Case Study from Permian Longtan Formation, Shuicheng, Guizhou - Debashish Mondal; Sijie Han; Shuxun Sang; Xiaozhi Zhou; Fuping Zhao; Wei Gao; Peiming Zhou; Jinchao Zhang; Ang Xu (Natural Resources Research, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Mapping conservation priorities for wild yak (Bos mutus) habitats on the Tibetan Plateau, China - Hang Zhao; Nai'ang Wang; Hongyi Cheng; Yipeng Wang; Xiao Liu; Bin Qiao; Liqiang Zhao (Science of The Total Environment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Design and fabrication of self-suspending aluminum-plastic/semiconductor photocatalyst devices for solar energy conversion - Zhi-Ang Zhao; Jingyun Mao; Chengjing Lu; Shuangqiao Yang; Qingrong Qian; Qinghua Chen; Hun Xue; Xiaoli Sun; Min-Quan Yang (Journal of Environmental Sciences, 2024)

Research on intelligent control theory and strategy of gas drainage pipe network based on graph theory - Aitao Zhou; Chang'ang Du; Kai Wang; Xihui Fan; Dongxu Wang; Wei Zhao; Han Gao (Fuel, 2024)

Effects of Environmental Heavy Metal Interactions on Renal Impairment: Epidemiological Evidence from Rural Northeastern China - Guohuan Yin; Xiaoyu Ge; Meiduo Zhao; Jing Xu; Ang Li; Yayuan Mei; Jingtao Wu; Xiaolin Liu; Lanping Wei; Qun Xu (Exposure and Health, 2023)

Differential effects of PM2.5 and its carbon components on blood pressure in hypertensive and non-hypertensive populations: a panel study in Beijing - Xue Wang; Ang Li; Meiduo Zhao; Jing Xu; Yayuan Mei; Qun Xu (Environmental Science and Pollution Research, 2023)

Comprehensive study on particle size distribution, MAH and PAH profiles during alkylbenzene pyrolysis - Pengcheng Zhao; Tie Li; Ang Li; Yongzhi Ma; Mingming Fang; Xinling Li (Fuel, 2023)

Reduced nitrogen fertilization from pre-flowering to pre-veraison alters phenolic profiles of Vitis vinifera L. Cv. Cabernet Gernischt wine of Yantai, China - Jianqiang Song; Ang Zhang; Fei Gao; Mingqing Li; Xianhua Zhao; Jie Zhang; Genjie Wang; Yuping Hou; Shiwei Cheng; Huige Qu; Shili Ruan; Jiming Li (Food Research International, 2023)

Thyroid disrupting effects of multiple metals exposure: Comprehensive investigation from the thyroid parenchyma to hormonal function in a prospective cohort study - Ang Li; Quan Zhou; Yayuan Mei; Jiaxin Zhao; Meiduo Zhao; Jing Xu; Xiaoyu Ge; Yanbing Li; Kai Li; Ming Yang; Qun Xu (Journal of Hazardous Materials, 2023)

Performance enhancement of proton exchange membrane fuel cells with bio-inspired gear-shaped flow channels - Yuzhi Ke; Baotong Zhang; Wei Yuan; Yafeng Bai; Yonghao Zhao; Zi'ang Liu; Zhenhe Lin; Xinze Li; Yangang Wang; Yong Tang (Chemical Engineering Journal, 2023)

Assessment of germplasm resource and detection of genomic signature under artificial selection of Zhikong scallop (Chlamys farreri) - Xuefeng Wang; Zujing Yang; Liming Jiang; Zhi Liu; Xixi Dong; Mingyi Sui; Chenlin Yin; Xiaojing Shen; Ang Zhao; Jingjie Hu; Zhenmin Bao; Liping Hu; et al. (Aquaculture, 2023)

A glance of coupled water and wastewater treatment systems based on microbial fuel cells - Yulong Huang; Yaqian Zhao; Cheng Tang; Asheesh Kumar Yadav; Rouzbeh Abbassi; Peiying Kang; Yamei Cai; Ang Liu; Anran Yang; Min Li (Science of The Total Environment, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Boosting photocatalytic activity of CdLa2S4/ZnIn2S4 S-scheme heterojunctions with spatial separation of photoexcited carries - Meng Dai; Huijun Yu; Wenhan Chen; Kongyu-Ang Qu; Dong Zhai; Chengcheng Liu; Shan Zhao; Shuguang Wang; Zuoli He (Chemical Engineering Journal, 2023)

Neurotoxicological mechanisms of carbon quantum dots in a new animal model Dugesia japonica - Jing Kang; Qing Ai; Ang Zhao; Haijiao Wang; Xiangpeng Zhang; Yanli Liu; Lingke Zhang; Yuqing Liu (Ecotoxicology, 2023)

Quantitative analysis of the minimum days of dietary survey to estimate dietary pesticide exposure: Implications for dietary pesticide sampling strategy - Ang Li; Ming Yang; Yayuan Mei; Quan Zhou; Jiaxin Zhao; Yanbing Li; Kai Li; Meiduo Zhao; Jing Xu; Qun Xu (Environmental Pollution, 2023)

DUSP2 Deletion Inhibits Macrophage Migration by Inhibiting ERK Activation in Zebrafish - Yu-Jiao Li; Xin-Liang Wang; Ling-Yu Shi; Zong-Yi Wang; Zi-Ang Zhao; Shu-Chao Ge; Bing Hu (Fishes, 2023)
Dual-specificity phosphatase 2 (DUSP2) regulates the activation of members of the mitogen-activated protein kinase (MAPK) family, which is involved in a variety of cellular processes including cell proliferation, differentiation, apoptosis, and migration. DUSP2 also regulates the expression of inflammatory mediators in macrophages; however, it remains unknown whether DUSP2 participates in macrophage migration. Here, using the tail fin injury model in zebrafish larvae, we found that the deletion of DUSP2 inhibited the expression of pro-inflammatory cytokines and macrophage chemokines. Moreover, live imaging results showed that the migration of macrophages to the injury site was inhibited after DUSP2 deletion. This inhibitory effect was mediated through the reduced activation of extracellular regulated protein kinases (ERK) in DUSP2 knockout zebrafish.

Intracellular electron competition in response to the oxygen pressure of the aerobic denitrification process in an O2-based membrane biofilm reactor (MBfR) for nitrate removal - Liang Feng; Fei-yun Sun; Jixian Yang; Di Cui; Zuo-hua Li; Shanshan Pi; He-Ping Zhao; Ang Li (Science of The Total Environment, 2023)

Modified Method for Calculating Saturation Gas Content in Deep Coal and the Pore Size Effect of Methane Adsorption on Guizhou Middle- and High-Rank Coals - Fuping Zhao; Sijie Han; Shuxun Sang; Peiming Zhou; Debashish Mondal; Zhijun Guo; Ang Xu (Natural Resources Research, 2023)

Effects of cascading reservoirs on streamflow and sediment load with machine learning reconstructed time series in the upper Yellow River basin - Junjian Fan; Guangju Zhao; Xingmin Mu; Ang Lu; Peng Tian; Peng Gao; Wenyi Sun (CATENA, 2023)

Associations of metals and metals mixture with lipid profiles: A repeated-measures study of older adults in Beijing - Ang Li; Yanbing Li; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Kai Li; Meiduo Zhao; Jing Xu; Xiaoyu Ge; Qun Xu (Chemosphere, 2023)

Integrated mRNA and miRNA expression analyses for Cryptocaryon irritans resistance in large yellow croaker (Larimichthys crocea) - Ang Qu; Yulin Bai; Jiaying Wang; Ji Zhao; Junjia Zeng; Yue Liu; Xintong Chen; Qiaozhen Ke; Pengxin Jiang; Xinyi Zhang; Xin Li; Peng Xu; et al. (Fish & Shellfish Immunology, 2023)

Sediment load estimation using a novel regionalization sediment-response similarity method for ungauged catchments - Raksmey Ang; Tsuyoshi Kinouchi; Wenpeng Zhao (Journal of Hydrology, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Variability, Clearance, and Concentration of Multiple Metals and Risk of Kidney Function Abnormality: A New Integrative Metal Exposure Assessment Approach - Ang Li; Jiaxin Zhao; Yayuan Mei; Quan Zhou; Meiduo Zhao; Jing Xu; Xiaoyu Ge; Qun Xu (Exposure and Health, 2023)

On the Key Dynamical Processes Supporting the 21.7 Zhengzhou Record-breaking Hourly Rainfall in China - Peng Wei; Xin Xu; Ming Xue; Chenyue Zhang; Yuan Wang; Kun Zhao; Ang Zhou; Shushi Zhang; Kefeng Zhu (Advances in Atmospheric Sciences, 2023)

Comparison of alive and dead benthic foraminiferal fauna off the Changjiang Estuary: Understanding water-mass properties and taphonomic processes - Feng Jiang; Daidu Fan; Quanhong Zhao; Yijing Wu; Fahui Ren; Yan Liu; Ang Li (Frontiers in Marine Science, 2023)
Benthic foraminifera (BF) are utilized in palaeo-environmental reconstruction based on our understanding of how living individuals respond to environmental variations. However, there is still a lack of empirical insight into how non-environmental factors, such as taphonomic processes, influence the preservations of fossil BF in strata. In this study, we compare the spatial distribution and composition of alive and dead BF fauna in surface sediments to elucidate how well fossil foraminiferal fauna mirror quasi-contemporary alive BF groups indicative of different water masses off a mega-river (Changjiang) estuary, which is characterized by intense and complex river-sea interactions. On-site measurements of bottom water salinity, temperature, and dissolved oxygen were conducted in the summer to determine water mass properties. A same-site comparison of alive (Rose Bengal stained) and dead foraminiferal fauna in surface sediment samples over 73 stations was then carried out. Q-mode Hierarchical clustering analysis was used to differentiate foraminiferal assemblages based on the relative abundance of common species. Three distinct regions with different water-mass properties were identified. The distribution pattern of dead foraminiferal fauna is mainly inherited from alive fauna, while the density and diversity of the dead fauna were found to be higher than those of the alive one. Both alive and dead fauna were clustered into four assemblages. A few common alive species (small-agglutinated and thin-calcareous) were rarely found in dead fauna, and a few common dead species (preferring low temperature and indicating allochthonous sources) were rarely present in alive fauna. The alive foraminiferal abundance and diversity were mainly determined by food resources and environmental properties of salinity and temperature. Alive foraminiferal assemblages were separated by different water masses determined by river-sea interactions off the Changjiang Estuary. The “time-averaging” effect was found to be responsible for the higher density and diversity of the dead fauna. Disintegration of agglutinated tests, dissolution of calcareous tests and selective transportation were observed to contribute to the different species compositions between the alive and dead fauna. Nevertheless, indicative species-environment relations in alive and taphocoenose fauna were found to be almost homologous among most common species. This suggests that distinct benthic foraminiferal assemblages can be used to effectively differentiate between different water masses in the study coastal seas.

Dual RNA-seq reveals a host-pathogen interaction transcriptional regulation pattern between Cryptocaryon irritans and large yellow croaker (Larimichthys crocea) - Yulin Bai; Yue Liu; Ang Qu; Jiaying Wang; Ji Zhao; Qiaozhen Ke; Xintong Chen; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Aquaculture, 2023)

Deciphering the genetic basis and prediction genomic estimated breeding values of heat tolerance in Zhikong scallop Chlamys farreri - Haitao Yu; Mingyi Sui; Zujing Yang; Chang Cui; Xiujiang Hou; Zhi Liu; Xuefeng Wang; Xixi Dong; Ang Zhao; Yangfan Wang; Xiaoting Huang; Jingjie Hu; et al. (Aquaculture, 2023)

Increasing diversity and biotic homogenization of lake plankton during recovery from acidification - Shuyu Jiang; Ting Hu; Wenqian Zhao; Ang Hu; Lifeng Zhu; Jianjun Wang (Science of The Total Environment, 2023)

Palaeoenvironmental evolution of the Badain Jaran Desert hinterland during the Early to Middle Holocene: A multi-proxy reconstruction on Taoerlegetu paleolake, northwest China - Chen’ao Lu; Nai'’ang Wang; Lvlv Zhang; Zhuolun Li; Wenwei Zhao; Meng Li; Xianbao Su; Yixin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Pollution profiles, influencing factors, and source apportionment of target and suspect organophosphate esters in ambient air: A case study in a typical city of Northern China - Ang Zhao; Chao Wei; Yue Xin; Xiaoli Wang; Qingqing Zhu; Jixing Xie; Haiyun Ma; Jianzhong Xu; Mei Wang (Journal of Hazardous Materials, 2023)

Trace elements and Alzheimer dementia in population-based studies: A bibliometric and meta-analysis - Kai Li; Ang Li; Yayuan Mei; Jiaxin Zhao; Quan Zhou; Yanbing Li; Ming Yang; Qun Xu (Environmental Pollution, 2023)

Identification and Expression Analysis of LncRNAs Reveal the Immune Mechanism of Visceral White-Nodules Disease Resistance in Large Yellow Croaker - Yulin Bai; Xintong Chen; Ang Qu; Yue Liu; Ji Zhao; Qiaozhen Ke; Fei Pu; Linni Wu; Hongshu Chi; Hui Gong; Tao Zhou; Peng Xu (Marine Biotechnology, 2023)

Association of long-term air pollution exposure with the risk of prediabetes and diabetes: Systematic perspective from inflammatory mechanisms, glucose homeostasis pathway to preventive strategies - Yayuan Mei; Ang Li; Jiaxin Zhao; Quan Zhou; Meiduo Zhao; Jing Xu; Runkui Li; Yanbing Li; Kai Li; Xiaoyu Ge; Chen Guo; Yongjie Wei; et al. (Environmental Research, 2023)

Associations and burdens of relative humidity with cause-specific mortality in three Chinese cities - Yayuan Mei; Ang Li; Meiduo Zhao; Jing Xu; Runkui Li; Jiaxin Zhao; Quan Zhou; Xiaoyu Ge; Qun Xu (Environmental Science and Pollution Research, 2023)

Phospholipase D and phosphatidic acid mediate regulation in the biosynthesis of spermidine and ganoderic acids by activating GlMyb in Ganoderma lucidum under heat stress - Xiaofei Han; Zi Wang; Lingyan Shi; Jing Zhu; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2022)
Polyamines are essential for all kinds of organisms and take part in the regulation of multiple biological processes. Our previous study revealed that heat stress promoted the conversion of putrescine to spermidine and subsequently promoted the accumulation of ganoderic acids (GAs). However, how heat stress affects polyamine homeostasis remains unclear. To explore the underlying mechanism by which heat stress promoted spermidine biosynthesis, we assessed the effects of signalling molecules that respond to heat stress on spermidine biosynthesis. Our data suggested that heat stress‐induced spermidine biosynthesis and GAs accumulation via a phospholipase D (PLD)‐mediated phosphatidic acid (PA) signal. Further research revealed that the transcription factor GlMyb promoted spermidine biosynthesis via regulating spermidine synthase genes ( spds1 and spds2 ) expression by directly bonding to their promoters and it responded to heat stress and PA signal. In summary, heat stress activated GlMyb by PLD‐mediated PA signalling and subsequently induced the expression of spds1 and spds2 to promote the biosynthesis of spermidine and the accumulation of GAs. Our findings firstly reveal a detailed mechanism by which heat signalling regulates polyamine homeostasis by PLD‐mediated PA signal in fungi and provide a greater understanding of how organisms alter polyamine levels in response to environmental changes.

Responses of grassland ecosystem carbon fluxes to precipitation and their environmental factors in the Badain Jaran Desert - Ping Yang; Nai’ang Wang; Liqiang Zhao; Bingjie Su; Zhenmin Niu; Hang Zhao (Environmental Science and Pollution Research, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Changes of precipitation pattern in China: 1961–2010 - Ang Zhang; Xinyi Zhao (Theoretical and Applied Climatology, 2022)

Response of net ecosystem CO2 exchange to precipitation events in the Badain Jaran Desert - Ping Yang; Liqiang Zhao; Xueran Liang; Zhenmin Niu; Hang Zhao; Yuanyuan Wang; Nai’ang Wang (Environmental Science and Pollution Research, 2022)

Improvement of laccase activity by silencing PacC in Ganoderma lucidum - Jing Zhu; Shuqi Song; Lindan Lian; Liang Shi; Ang Ren; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2022)

Optimizing Microalgae Diet, Temperature, and Salinity for Dwarf Surf Clam, Mulinia lateralis, Spat Culture - Zujing Yang; Hao Wang; Moli Li; Mingxuan Teng; Xuefeng Wang; Ang Zhao; Xiaoting Huang; Jingjie Hu; Zhenmin Bao (Frontiers in Marine Science, 2022)
Dwarf surf clam, Mulinia lateralis , is widely considered as a model species for bivalves. The development of a standard culture system could greatly promote the production of high-quality individuals, yet information on the culture conditions for M. lateralis spat is still limited. This study aims to determine the suitable microalgae diet, temperature, and salinity for M. lateralis spat culture. The typically fed microalgae species, including Chlorella pyrenoidesa (Cp), Platymonas helgolandica (Ph), Dunaliella salina (Ds), Nitzschia closterium (Nc), and Chaetoceros muelleri (Cm), could be taken up by M. lateralis spat, and their filtration rates on Cp, Nc, and Cm were higher than those on Ds and Ph. For the entire spat culture, all diet trials showed similar survival percentages, while the mono-specific diet Cp exhibited the highest growth rate, suggesting that Cp was the optimal microalgae species for M. lateralis spat. Through simultaneously maximizing the growth and survival of spat, the optimal microalgae concentration and stocking density were 5 × 10 4 cells ml –1 and 400–600 individuals m –2 for 30–40-day-old spat as well as 1 × 10 5 cells ml –1 and 400–600 individuals m –2 for 40–50-day-old spat, respectively. In addition, the spat had higher growth rates and survival percentages at the temperature of 20–22°C and salinity of 22–25 ppt. The results of this study provide a basis for further culture of M. lateralis spat, and the optimized conditions will be of great significance for the construction of the standard culture system of M. lateralis .

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Developing the non‐dimensional framework for water distribution formulation to evaluate sprinkler irrigation* - Ang Li; Xinyuan Mu; Xia Zhao; Jiamin Xu; Majid Khayatnezhad; Reza Lalehzari (Irrigation and Drainage, 2021)
Improving the application efficiency and leaching of solutes from the root zone in a sprinkler irrigation system are directly related to the uniformity of water distribution at the field surface. The coefficient of uniformity and distribution uniformity are affected by changes in wind speed and its direction, sprinkler characteristics and variations in operating pressure. The objective of this paper is to present modified equations for evaluating pressurized irrigation systems based on non‐dimensional infiltrated depths. The equations were obtained by four data groups including the average of the measured infiltration depths in any quarter. Coefficient of uniformity (CU), distribution uniformity (DU), application efficiency ( E a ) and deep percolation (DP) were used as performance indicators to evaluate the sprinkler irrigation system. The suggested method was compared to the existing approach to assess the evaluation indicators. Three data sets of observed information for wheel‐move, permanent solid set and semi‐solid set irrigation systems were collected in Chaharmahal and Bakhtiari provinces to evaluate the proposed formulation. Furthermore, the relationships between CU and DU were analysed for three scenarios of infiltration depth. Results show that the application efficiency was 12% less than previous equations because of using four average values.

A New Scheme of Adaptive Covariance Inflation for Ensemble Filtering Data Assimilation - Ang Su; Liang Zhang; Xuefeng Zhang; Shaoqing Zhang; Zhao Liu; Caili Liu; Anmin Zhang (Journal of Marine Science and Engineering, 2021)
Due to the model and sampling errors of the finite ensemble, the background ensemble spread becomes small and the error covariance is underestimated during filtering for data assimilation. Because of the constraint of computational resources, it is difficult to use a large ensemble size to reduce sampling errors in high-dimensional real atmospheric and ocean models. Here, based on Bayesian theory, we explore a new spatially and temporally varying adaptive covariance inflation algorithm. To increase the statistical presentation of a finite background ensemble, the prior probability of inflation obeys the inverse chi-square distribution, and the likelihood function obeys the t distribution, which are used to obtain prior or posterior covariance inflation schemes. Different ensemble sizes are used to compare the assimilation quality with other inflation schemes within both the perfect and biased model frameworks. With two simple coupled models, we examined the performance of the new scheme. The results show that the new inflation scheme performed better than existing schemes in some cases, with more stability and fewer assimilation errors, especially when a small ensemble size was used in the biased model. Due to better computing performance and relaxed demand for computational resources, the new scheme has more potential applications in more comprehensive models for prediction initialization and reanalysis. In a word, the new inflation scheme performs well for a small ensemble size, and it may be more suitable for large-scale models.

Swi6B , an alternative splicing isoform of Swi6, mediates the cell wall integrity of Ganoderma lucidum - Lingdan Lian; Guang Zhang; Jing Zhu; Yunxiao Wang; Lingshuai Wang; Rui Liu; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary The cell wall integrity (CWI) signaling activates the transcription factor Swi6 through a MAPK signaling cascade in response to cell wall stresses. In this study, we observed two different mRNA variants of swi6 ( GlSwi6A and GlSwi6B ) existed, due to alternative splicing. Besides, the expression level of GlSwi6B was higher than that of the GlSwi6A mRNA variant. The co‐silencing of GlSwi6A and GlSwi6B was more sensitive to cell wall stress compared with WT, resulting in a decrease of 78% and 76% in chitin and β‐1,3‐ d ‐glucan content respectively. However, only the overexpression of GlSwi6B decreased the sensitivity to cell wall stress and increased the content of chitin and β‐1,3‐ d ‐glucan compared with the WT strain. Furthermore, Y1H, EMSA and BLI assays revealed that the GlSwi6B could bind to the promoters of chitin and glucan synthesis genes (GL24454 and GL18134). However, the binding phenome has not been observed in the isoform GlSwi6A. Taken together, our results found two different transcripts generated from Swi6 , in which the alternative splice isoform of GlSwi6B participates in regulating the CWI of G . lucidum . This study provides the first insight into the alternative splicing isoform of GlSwi6B in the regulation of CWI signaling in fungi.

Antimonate removal by diatomite modified with Fe-Mn oxides: application and mechanism study - Qiu-Yi Dong; Yu-Chun Fang; Bin Tan; Aura Ontiveros-Valencia; Ang Li; He-Ping Zhao (Environmental Science and Pollution Research, 2021)

Regulation of glutamine synthetase activity by transcriptional and posttranslational modifications negatively influences ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Shuqi Song; Zehua Sun; Lingdan Lian; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Glutamine synthetase (GS), a central nitrogen metabolic enzyme, plays important roles in the nitrogen regulation network and secondary metabolism in fungi. However, the mechanisms by which external nitrogen sources regulate fungal GS activity have not been determined. Here, we found that GS activity was inhibited under nitrate conditions in Ganoderma lucidum . By constructing gs ‐silenced strains and adding 1 mM GS inhibitor to inhibit GS activity, we found that a decrease in GS activity led to a decrease in ganoderic acid biosynthesis. The transcription of gs increased approximately five fold under nitrate conditions compared with that under ammonia. Electrophoretic mobility shift and yeast one‐hybrid assay showed that gs was transcriptionally regulated by AreA. Although both gs expression and GS protein content increased under nitrate conditions, the GS activity still decreased. Treatment of recombinant GS with SIN‐1 (protein nitration donor) resulted in a strengthened nitration accompanied by a 71% decrease in recombinant GS activity. Furthermore, intracellular GS could be nitrated from mycelia cultivated under nitrate conditions. These results indicated that GS activity could be inhibited by NO‐mediated protein nitration. Our findings provide the first insight into the role of transcriptional and posttranslational regulation of GS activity in regulating secondary metabolism in fungi.

Nitric oxide regulates ganoderic acid biosynthesis by the S‐nitrosylation of aconitase under heat stress in Ganoderma lucidum - Rui Liu; Ting Zhu; Tao Yang; Zhengyan Yang; Ang Ren; Liang Shi; Jing Zhu; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Nitric oxide (NO) is an important signalling molecule in stress response of organisms. We previously reported that NO decreases heat stress (HS)‐induced ganoderic acid (GA) accumulation in Ganoderma lucidum . To explore the mechanisms by which NO modulates GA biosynthesis under HS, the effect of NO on the reactive oxygen species (ROS) content was examined. The results showed that NO decreased the production of mitochondrial ROS (mitROS) by 60% under HS. Further research revealed that NO reduced the mitROS content by inhibiting aconitase (Acon) activity. The GA content in Acon‐silenced (Aconi) strains treated with NO donor did not differ significantly from that in untreated Aconi strains. To study the mechanism by which Acon activity is inhibited, the S‐nitrosylation level of Acon was determined. Biotin‐switch technology and mass spectrometry analysis were used to show that Acon is S‐nitrosylated at the Cys‐594 amino acid residue. Substitution of Cys‐594 with a Ser, which cannot be S‐nitrosylated, abolished the responsiveness of Acon to the NO‐induced reduction in its enzymatic activity. These findings demonstrate that NO inhibits Acon activity through S‐nitrosylation at Cys‐594. In summary, these findings describe mechanism by which NO regulates GA biosynthesis via S‐nitrosylation of Acon under HS condition in G . lucidum .

Deinococcus detaillensis sp. nov., isolated from humus soil in Antarctica - Kun Zhang; Jing Zhu; Shuai Li; Manik Prabhu Narsing Rao; Ning-Mei Li; Ang-Yang Guo; Zhao Jiang; Qi-Yong Tang; Yi Wan; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2020)

OP16 induces deadly autophagy and apoptosis of cells by inhibiting Akt in esophageal squamous cell carcinoma - Guiqin Hou; Ang Jia; Li Yang; Yu Zhao; Yi Hu; Wuduo Zhao; Wen Zhao; Hong-Min Liu; Zhaoming Lu (Molecular and Cellular Biochemistry, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

In Ganoderma lucidum , Glsnf1 regulates cellulose degradation by inhibiting GlCreA during the utilization of cellulose - Yanru Hu; Wenzhao Xu; Shishan Hu; Lingdan Lian; Jing Zhu; Liang Shi; Ang Ren; MingWen Zhao (Environmental Microbiology, 2020)
Summary Cellulose is a by‐product of agricultural production and an abundant waste. As a carbon source, cellulose can be degraded and utilized by fungi. Carbon sources, which act as nutrients, not only provide energy but also serve as regulators of gene expression, metabolism and growth, through various signalling networks that enable cells to sense and adapt to varying environmental conditions. Nutrient‐sensing pathways prioritize the use of preferred carbon sources and regulate the production of cellulose‐degrading enzymes when necessary. Understanding the regulation of the fungal cellulolytic response will become increasingly important because we strive to increase the efficiency of the utilization of these renewable energy sources. Here, we show that Glsnf1, a sucrose‐nonfermenting serine–threonine‐protein kinase 1 (Snf1)/AMP‐activated protein kinase homologue in medicinal macro basidiomycete Ganoderma lucidum , actively responds to carbon alterations and positively regulates cellulase activity and cellulase‐related gene transcription. The carbon catabolite repressor CreA, a zinc binuclear cluster transcription factor that mediates the sensing of nutrients and suppression of the transcription of a number of genes necessary for the consumption of a less preferred carbon source, participates in the Glsnf1‐mediated regulation of cellulases. Glsnf1 not only negatively regulates the transcription level of the CreA gene but also hinders its localization in the nucleus. Overall, our findings reveal a key nutrient‐sensing mechanism that is critical for the modulation of carbon source adaptation in G . lucidum .

The mediated role of complement C3 in PM2.5 exposure and type 2 diabetes mellitus: an elderly panel study in Beijing, China - Yuanren Tong; Lu Pei; Kai Luo; Meiduo Zhao; Jing Xu; Ang Li; Runkui Li; Mingan Yang; Qun Xu (Environmental Science and Pollution Research, 2019)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Dual functions of AreA, a GATA transcription factor, on influencing ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Zehua Sun; Dengke Shi; Shuqi Song; Lingdan Lian; Liang Shi; Ang Ren; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2019)
Summary Nitrogen metabolism repression (NMR) has been well studied in filamentous fungi, but the molecular mechanism of its effects on fungal secondary metabolism has been generally unexplored. Ganoderic acid (GA) biosynthesis in Ganoderma lucidum differs between ammonia and nitrate nitrogen sources. To explain the functions of NMR in secondary metabolism, AreA, which is a core transcription factor of NMR, was characterized in G . lucidum . The transcription level of AreA was dramatically increased (approximately 4.5‐folds), with the nitrate as the sole nitrogen source, compared with that with ammonia as the source. In addition, the expression of related genes involved in NMR was changed (upregulated of MeaB and downregulated of Nmr and GlnA ) when AreA was knockdown. Yeast one‐hybrid and electrophoretic mobility shift assay results showed that AreA could directly bind to the promoter of fps (encoding farnesyl‐diphosphate synthase) to activate its expression. However, GA biosynthesis was increased (27% in the ammonia source and 77% in the nitrate source) in AreAi mutant strains versus that in control strains. These results showed that another important factor must participate in regulating GA biosynthesis other than the direct activation of AreA. Furthermore, we found that the content of nitric oxide (NO) was increased approximately 2.7‐folds in the nitrate source compared with that in the ammonia. By adding the NO donor (SNP) or scavenger (cPTIO) and using NR ‐silenced or NR ‐overexpressed strains, we found that there was a negative correlation between the NO contents and GA biosynthesis. NO generated by nitrate reductase (NR) during the nitrogen utilization burst and could negatively influence GA biosynthesis. As a global transcription factor, AreA could also regulate the expression of NR . Our studies provide novel insight into the dual functions of AreA in GA biosynthesis during nitrogen assimilation.

14-3-3 Proteins: a window for a deeper understanding of fungal metabolism and development - Liang Shi; Ang Ren; Jing Zhu; Hanshou Yu; Ailiang Jiang; Huihua Zheng; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2019)

Conversion of phosphatidylinositol (PI) to PI4‐phosphate (PI4P) and then to PI(4,5)P 2 is essential for the cytosolic Ca 2+ concentration under heat stress in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2018)
Summary How cells drive the phospholipid signal response to heat stress (HS) to maintain cellular homeostasis is a fundamental issue in biology, but the regulatory mechanism of this fundamental process is unclear. Previous quantitative analyses of lipids showed that phosphatidylinositol (PI) accumulates after HS in Ganoderma lucidum , implying the inositol phospholipid signal may be associated with HS signal transduction. Here, we found that the PI‐4‐kinase and PI‐4‐phosphate‐5‐kinase activities are activated and that their lipid products PI‐4‐phosphate and PI‐4,5‐bisphosphate are increased under HS. Further experimental results showed that the cytosolic Ca 2+ ([Ca 2+ ] c ) and ganoderic acid (GA) contents induced by HS were decreased when cells were pretreated with Li + , an inhibitor of inositol monophosphatase, and this decrease could be rescued by PI and PI‐4‐phosphate. Furthermore, inhibition of PI‐4‐kinases resulted in a decrease in the Ca 2+ and GA contents under HS that could be rescued by PI‐4‐phosphate but not PI. However, the decrease in the Ca 2+ and GA contents by silencing of PI‐4‐phosphate‐5‐kinase could not be rescued by PI‐4‐phosphate. Taken together, our study reveals the essential role of the step converting PI to PI‐4‐phosphate and then to PI‐4,5‐bisphosphate in [Ca 2+ ] c signalling and GA biosynthesis under HS.

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

Phospholipase D and phosphatidic acid mediate heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Dai Chen; Ya‐Ping Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Phospholipid‐mediated signal transduction plays a key role in responses to environmental changes, but little is known about the role of phospholipid signalling in microorganisms. Heat stress (HS) is one of the most important environmental factors. Our previous study found that HS could induce the biosynthesis of the secondary metabolites, ganoderic acids (GA). Here, we performed a comprehensive mass spectrometry‐based analysis to investigate HS‐induced lipid remodelling in Ganoderma lucidum . In particular, we observed a significant accumulation of phosphatidic acid (PA) on HS. Further genetic tests in which pld ‐silencing strains were constructed demonstrated that the accumulation of PA is dependent on HS‐activated phospholipase D (PLD) hydrolysing phosphatidylethanolamine. Furthermore, we determined the role of PLD and PA in HS‐induced secondary metabolism in G . lucidum . Exogenous 1‐butanol, which decreased PLD‐mediated formation of PA, reverses the increased GA biosynthesis that was elicited by HS. The pld ‐silenced strains partly blocked HS‐induced GA biosynthesis, and this block can be reversed by adding PA. Taken together, our results suggest that PLD and PA are involved in the regulation of HS‐induced secondary metabolism in G . lucidum . Our findings provide key insights into how microorganisms respond to heat stress and then consequently accumulate secondary metabolites by phospholipid remodelling.

Membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Tian‐Jun Zhang; Xiao‐Xiao Lu; Bao‐Liang Ma; Ang Ren; Liang Shi; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum has become a potential model system for evaluating how environmental factors regulate the secondary metabolism of basidiomycetes. Heat stress (HS) is one of the most important environmental factors. It was previously reported that HS could induce the biosynthesis of ganoderic acids (GA). In this study, we found that HS increased GA biosynthesis and also significantly increased cell membrane fluidity. Furthermore, our results showed that addition of the membrane rigidifier dimethylsulfoxide (DMSO) could revert the increased GA biosynthesis elicited by HS. These results indicate that an increase in membrane fluidity is associated with HS‐induced GA biosynthesis. Further evidence showed that the GA content was decreased in D9des ‐silenced strains and could be reverted to WT levels by addition of the membrane fluidizer benzyl alcohol (BA). In contrast, GA content was increased in D9des ‐overexpression strains and could be reverted to WT levels by the addition of DMSO. Furthermore, both membrane fluidity and GA biosynthesis induced by HS could be reverted by DMSO in WT and D9des ‐silenced strains. To the best of our knowledge, this is the first report demonstrating that membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in filamentous fungi.

Ethylene promotes mycelial growth and ganoderic acid biosynthesis in Ganoderma lucidum - Guang Zhang; Ang Ren; Fengli Wu; Hanshou Yu; Liang Shi; Mingwen Zhao (Biotechnology Letters, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Dose, Plasma Level, and Treatment Outcome Among Methadone Patients in Shanghai, China - Haifeng Jiang; Maureen Hillhouse; Jiang Du; Shujun Pan; Ang Alfonso; Jun Wang; Zhirong Zhou; Weijun Yuan; Walter Ling; Min Zhao (Neuroscience Bulletin, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

A step through the looking glass - Youyun Liang; Ee Lui Ang; Huimin Zhao (Science China Life Sciences, 2016)

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

The bacterial lipopeptide iturins induce V erticillium dahliae cell death by affecting fungal signalling pathways and mediate plant defence responses involved in pathogen‐associated molecular pattern‐triggered immunity - Qin Han; Fengli Wu; Xiaonan Wang; Hong Qi; Liang Shi; Ang Ren; Qinghai Liu; Mingwen Zhao; Canming Tang (Environmental Microbiology, 2015)
Summary V erticillium wilt in cotton caused by V erticillium dahliae is one of the most serious plant diseases worldwide. Because no known fungicides or cotton cultivars provide sufficient protection against this pathogen, V . dahliae causes major crop yield losses. Here, an isolated cotton endophytic bacterium, designated B acillus amyloliquefaciens 41 B ‐1, exhibited greater than 50% biocontrol efficacy against V . dahliae in cotton plants under greenhouse conditions. Through high‐performance liquid chromatography and mass analysis of the filtrate, we found that the antifungal compounds present in the strain 41 B ‐1 culture filtrate were a series of isoforms of iturins. The purified iturins suppressed V . dahliae microsclerotial germination in the absence or presence of cotton. Treatment with the iturins induced reactive oxygen species bursts, H og1 mitogen‐activated protein kinase (MAPK) activation and defects in cell wall integrity. The oxidative stress response and high‐osmolarity glycerol pathway contribute to iturins resistance in V . dahliae . In contrast, the S lt2 MAPK pathway may be involved in iturins sensitivity in this fungus. In addition to antagonism, iturins could induce plant defence responses as activators and mediate pathogen‐associated molecular pattern‐triggered immunity. These findings suggest that iturins may affect fungal signalling pathways and mediate plant defence responses against V . dahliae .

Transcript and metabolite alterations increase ganoderic acid content in Ganoderma lucidum using acetic acid as an inducer - Ang Ren; Xiong-Biao Li; Zhi-Gang Miao; Liang Shi; Ai-Liang Jaing; Ming-Wen Zhao (Biotechnology Letters, 2014)

Functions of the nicotinamide adenine dinucleotide phosphate oxidase family in G anoderma lucidum : an essential role in ganoderic acid biosynthesis regulation, hyphal branching, fruiting body development, and oxidative‐stress resistance - Dashuai Mu; Chenyang Li; Xuchen Zhang; Xiongbiao Li; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2014)
Summary G anoderma lucidum has drawn worldwide interest with regard to its secondary metabolism and pharmaceutical activity. However, the development of such research has been limited because of a lack of basic biological knowledge. Nicotinamide adenine dinucleotide phosphate oxidases (Nox) have recently been highlighted because of the many important biological roles in plants and animals; however, the exact functions of Nox are still not fully understood in fungi. In this study, we identified two N ox isoforms ( NoxA and NoxB ) and a regulator, NoxR . RNA interference was used, and silencing of the Nox isoforms and NoxR expression indicated a central role for these genes in hyphal branching, fruiting body development, reactive oxygen species ( ROS ) generation, ROS resistance and ganoderic acid biosynthesis regulation. Further mechanistic investigation revealed that N ox‐generated ROS elevated cytosolic Ca 2+ levels by activating a plasma membrane Ca 2+ influx pathway, thereby inducing the Ca 2+ signal pathway to regulate ganoderic acid biosynthesis and hyphal branching. Importantly, our results highlight the N ox functions in signal crosstalk between ROS and Ca 2+ , and these findings provide an excellent opportunity to identify the potential pathway linking ROS networks to calcium signalling in fungi and suggest that plants, animals and fungi share a conserved signal‐crosstalk mechanism.

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

Molecular cloning, characterization, and function analysis of a mevalonate pyrophosphate decarboxylase gene from Ganoderma lucidum - Liang Shi; Lei Qin; Yingjie Xu; Ang Ren; Xing Fang; Dashuai Mu; Qi Tan; Mingwen Zhao (Molecular Biology Reports, 2012)

Development of a simple and efficient transformation system for the basidiomycetous medicinal fungus Ganoderma lucidum - Liang Shi; Xing Fang; Mengjiao Li; Dashuai Mu; Ang Ren; Qi Tan; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2012)

Early development of germlings of Sargassum thunbergii (Fucales, Phaeophyta) under laboratory conditions - Ziguo Zhao; Fengjuan Zhao; Jianting Yao; Jingmei Lu; Put. O. Ang; Delin Duan (Journal of Applied Phycology, 2008)

Genetic structure analysis of natural Sargassum muticum (Fucales, Phaeophyta) populations using RAPD and ISSR markers - Fengjuan Zhao; Fuli Liu; Jidong Liu; Put O. Ang; Delin Duan (Journal of Applied Phycology, 2008)